Culturally Responsive Pedagogy: A Canadian Perspective - Stephanie Chitpin; Olfa Karoui (Ali Khorsandi Taskoh, 2021)
In the Canadian province of Saskatchewan, the Ministry of Education has encouraged sociocultural and linguistic diversity within schools. Yet, as is typical within neoliberal societies, standardized assessments continue to be promoted for evaluating student progress and for the validity of in-school assessments. Standardized testing is designed using a monolingual Eurocentric perspective which ultimately discounts many cognitive processes used by non-Canadian EAL students. This study describes ways in which educational leaders work towards incorporating culturally responsive pedagogy into their practices so as to increase representativeness within their schools. Six principals in rural Saskatchewan were interviewed. Results revealed three common themes: the use of standardized data to assess student progress and in-school testing, integration of cultural competence practices, and initiation of individualized intervention strategies.